Insolvency law in times of COVID-19 - GURREA-MARTINEZ, Aurelio (Institutional Knowledge at Singapore Management University, 2020)
The international spread of the coronavirus is not only generating dramatic consequences from a social perspective but it is also heavily affecting the global economy. For this reason, governments, financial regulators and international organizations are responding to the coronavirus with a package of legal, economic and financial measures. Among the legal responses included in these packages, many countries, such as Australia, Belgium, Colombia, Czech Republic, France, Germany, Luxembourg, India, Italy, New Zealand, Peru, Poland, Portugal, Russia, Singapore, Spain, the United Kingdom, and the United States, have proposed or implemented temporary changes to their insolvency frameworks. This paper starts by discussing whether using the insolvency system should be the optimal solution to deal with companies affected by the coronavirus. For that purpose, it will analyze the role and limits of insolvency law. It then discusses the most relevant insolvency reforms taking place around the world as a response to the global pandemic, as well as other insolvency and insolvency-related reforms that could be implemented to minimize the harmful economic effects of COVID-19. The paper will conclude by arguing that, even though these measures can provide companies and corporate directors with a valuable breathing space, these reforms need to be accompanied by a more comprehensive package of legal, financial, tax and economic responses.